The term structure of interest rates : an expectations model tested on post-war Italian data - Masera, R. S. (Oxford : Clarendon Press, 1972)
The book adopted an expectational approach to explain yield differentials among fixed-interest securities of different maturities.
A revision of the author's thesis, Oxford, 1969.
Bibliography: p. [205]-211.
ucj 14/01/2019
Loans
Keywords: Interest rates; Interest rates